2003
DOI: 10.1038/sj.ejcn.1601603
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan decreases total cholesterol in women: a randomized, double-blind, placebo-controlled trial

Abstract: Background: Hypercholesterolemia is an important risk factor for cardiovascular disease. Orally administered chitosan binds lipids in the small intestine and reduces their absorption. Chitosan has been shown to decrease serum cholesterol in animal and human studies. This study investigated the effectiveness of chitosan in reducing serum cholesterol without concomitant diet therapy. Methods: Ninety female volunteers (age 34 -70 y) with confirmed mild to moderate hypercholesterolemia were enrolled into the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 20 publications
4
72
0
2
Order By: Relevance
“…Cônsolo et al (2015) fed increasing doses of WS to Nellore bulls and found a linear increase in total cholesterol and no difference in glucose concentrations. The mechanism by which CHI alters the cholesterol metabolism is unclear, but studies in humans have demonstrated that chitosan reduced serum LDL cholesterol (Yihua and Binglin, 1997;Wuolijoki et al, 1999), and Bokura and Kobayashi (2003) suggested a reduced lipid absorption from the gastrointestinal tract. However, the difference between EE digestion between CO and CHI was only 13 g kg −1 in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Cônsolo et al (2015) fed increasing doses of WS to Nellore bulls and found a linear increase in total cholesterol and no difference in glucose concentrations. The mechanism by which CHI alters the cholesterol metabolism is unclear, but studies in humans have demonstrated that chitosan reduced serum LDL cholesterol (Yihua and Binglin, 1997;Wuolijoki et al, 1999), and Bokura and Kobayashi (2003) suggested a reduced lipid absorption from the gastrointestinal tract. However, the difference between EE digestion between CO and CHI was only 13 g kg −1 in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan can be used as a functional ingredient as it acts as a gelling agent, emulsifier and food preservative (Borderıas et al 2005). Its ability to absorb fat creates a new potential for use as an anticholesterol agent (Bokura and Kobayashi 2003). Incorporation of chitosan into foods like biscuits (Maezaki et al 1993), meat products (Jo et al 2001;Lin and Chao 2001), fish muscle (Benjakul et al 2003;Kamil et al 2002) and derivative products such as fish patties and sausages (Lopez-Caballero et al 2005a, b) have been reported.…”
Section: Meat Incorporated Foodmentioning
confidence: 99%
“…Though it is not dissolved in organic solvents, neutral and alkali pH's, it can be dissolved in diluted acids (Chandy, Sharma, 1990). Chitosan becomes positively charged when the free amino groups, which it naturally possesses, turn into a soluble state because of their protonation in acidic conditions, as a result of which it may react with negatively charged polymers or negatively charged surfaces such as mucosa and substrates such as fats and lipids in gastrointestinal tract that may affect lipid concentration (Bokura, Kobayashi, 2003;Hejazi, Amiji, 2003;Sumiyoshi, Kimura, 2006;Anraku et al, 2010). Chitosan is an anti-allergenic polymer which is biologically compatible with living tissues, and biodegradable.…”
Section: Introductionmentioning
confidence: 99%